Analisis Ekstraks Ciri Fertilitas Telur Ayam Kampung dengan Grey Level Cooccurrence Matrix - Shoffan Saifullah; Sunardi Sunardi; Anton Yudhana (JURNAL NASIONAL TEKNIK ELEKTRO, 2017)
This research used chicken eggs to perform the analysis in the identification process fertility chicken eggs. The method in the identification process using Gray Level Co-occurrence Matrix (GLCM). The identification process by using GLCM using the 6 main parameters to determine the characteristics (feature extraction). The parameters used are: ASM (Angular Second Moment), Contrast, Correlation, Variance, IDM (Inverse Difference Moment), and Entropy. Each parameter will give different values and is able to distinguish and classify images based fertility chicken eggs chicken eggs. The identification process gives results that the image of a chicken egg fertile and infertile able to distinguish from GLCM parameters and show that using 10 samples of chicken eggs able to be grouped based on their fertility.Keywords:Chicken Eggs, Feature Extraction, GLCM ParametersAbstrak— Penelitian ini menggunakan telur ayam kampung untuk melakukan analisis dalam proses identifikasi fertilitas telur ayam. Metode dalam proses identifikasi menggunakan Gray Level Coocurence Materik (GLCM). Proses identifikasi dengan menggunakan GLCM menggunakan 6 parameter utama untuk mengetahui ciri-ciri (ekstraksi ciri). Parameter yang digunakan yaitu: ASM, Kontras, Korelasi, Varians, IDM, dan Entropy. Masing-masing parameter akan memberikan nilai yang berbeda dan mampu membedakan dan mengelompokkan citra telur ayam kampung berdasarkan fertilitas telur ayam. Proses identifikasi memberikan hasil bahwa citra teluer ayam kampung fertile dan infertile mampu dibedakan dengan parameter-parameter GLCM dan menunjukkan bahwa dengan menggunakan 10 sampel telur ayam kampung mampu dikelompokkan berdasaarkan fertilitasnya.Kata Kunci : Telur ayam kampung, Ekstraksi Ciri, Parameter GLCM